IMPLEMENTASI KINESIK, PROKSEMIK, PARALINGUISTIK DAN SELF DISCLOSURE DALAM KOMUNIKASI ANTARPRIBADI - Taufik - Rahman (Universitas Bunda Mulia, 2021)
Interpersonal communication that we have done in daily communication actually neet to be notice. For instance about self disclosure. Closer someone to another one in communication, self disclosure will arised. Kinesics is another example that actually attached in interpersonal communication. Facial expressions in happiness when speaking definitely different in otherwise situation. Individual involvement with the environment and using space in communication are another important thing in interpersonal communication related with proxemics. In another hand, paralinguistic gives a bold combination about communicator situation in communication process. All element above truly will advantages us if we can understand and use it for good communication purpose.